PENYUSUNAN STRATEGI E-GOVERNMENT BERBASIS KERANGKA KERJA PEMERINGKATAN E-GOVERNMENT INDONESIA (PEGI) DI LEMBAGA PENERBANGAN DAN ANTARIKSA NASIONAL - Fahmi Alusi; Dana Indra Sensuse (Faculty of Computer Science Universitas Indonesia, 2014)
Abstrak People's presures for establishing good governance motivate the government to be able quickly determine a right strategy to accelerate achievement of the government goals. One of strategies implemented in government is developing e-government, as stated in the Presidential Instruction No. 3 of 2003 on National Policy and Strategy Development of e-government. A framework used to measure level of development and implementation of e-government in Indonesian government institutions is PeGI (The ranking of e-government of Indonesia). To be able perform the implementation and development of e-government in a timely and effectively, it needs some strategies. This research aims to devise an e-government development strategy based on the PeGI framework by doing a case study on the National Institute of Aeronautics and Space (LAPAN). The methodology used is descriptive qualitative with data collection methods including document analysis, observations, and focus group discussion (FGD). Based on the analysis, it is found that the level of e-government implementation in LAPAN today is 1.88 while the level of e-government implementation expected is 3.18. Finally, this study described the strategies in LAPAN to reach the level of implementation of e-government as expected.